Pengetahuan Siklus Hidup Nyamuk Aedes aegypti untuk Cegah DBD Bagi Warga RT 44 Kelurahan Guntung Manggis Banjarbaru - Muhamat Muhamat; Gunawan Guawan (Universitas Lambung Mangkurat, 2023)
Abstract Dengue Hemorrhagic Fever (DHF) is still a health problem for the people of Banjarbaru. This disease can be prevented by avoiding the bite of the Aedes aegypti mosquito. The mosquito population of Ae. aegypti has a high potential to carry out biting activities. Therefore, mosquito control is the main focus in controlling DHF. The one house one larva monitor program by carrying out 3M activities (bury, cover and drain) water containers is relatively effective. However, knowledge about the life cycle is not the same among residents, so the implementation of this program is still constrained. With this background, the Lambung Mangkurat University Faculty of Mathematics and Natural Sciences service team held counseling for Dasa Wisma Jasmine 5 about the life cycle of the Aedes aegypti mosquito. The implementation of this service provides insight into the life cycle of the Aedes aegypti mosquito followed by the practice of trapping mosquito eggs. The hope of this program is to increase knowledge, change attitudes and take action in residential areas so that they do not become breeding grounds for the Aedes aegypti mosquito. Keywords: DHF disease; Aedes aegypti; knowledge; attitude; action